Clinical significance of 'double-hit' and 'double-expression' lymphomas. Issue 3 (15th October 2019) - Ma, Zhiping; Niu, Jing; Cao, Yanzhen; Pang, Xuelian; Cui, Wenli; Zhang, Wei; Li, Xinxia
Abstract : Background: 'Double-hit' lymphoma (DHL) and 'double-expression' lymphoma (DEL) involving gene rearrangement and protein expression of MYC and BCL2/BCL6 have recently become the most commonly used terms to describe the poor prognostic types of diffuse large B-cell lymphoma (DLBCL). However, the clinical and pathological spectra of these rare entities have not been well defined. The aim of this study was to determine the frequency of DHL and DEL in DLBCL and their prognostic impacts in the era of cyclophosphamide, doxorubicin, vincristine and prednisone plus rituximab therapy. Methods: The data and tissues from 98 patients diagnosed with DLBCL were used in this study. Formalin-fixed and paraffin-embedded tissues were constructed for immunohistochemistry (IHC) and interphase fluorescene in situ hybridisation (FISH) analysis for MYC, BCL6 and BCL2 rearrangements. Results: There were 14 cases (14.29%, 14/98) and 34 cases (34.70%, 34/98) of lymphomas with the DHL and DEL of MYC and BCL2/BCL6, respectively. DLBCL patients with MYC/BCL2 rearrangements more frequently had bone marrow involvement (p=0.002), and their tumours were commonly of the germinal centre B cell (GCB) subtype. Patients with MYC+/BCL2 +coexpression were more often assessed using the International Prognostic Index (IPI), (Performance Status) PS score and bone marrow involvement. Patients with MYC+/BCL6 +coexpression were associated with their IPI values, Eastern Cooperative Oncology Group scores and occurrence of B symptoms. Their lymphomas were more often of the non-GCB subtype (p=0.010). Multivariate analysis showed that IPI, bone marrow involvement, rearrangements of BCL2, BCL6 and MYC, expression concurrent with rearrangements and coexpression were all significantly associated with overall survival and progression-free survival, with the exception of MYC+/BCL6 +coexpression. Conclusions: MYC/BCL2 DHL, MYC/BCL6 DHL and MYC/BCL2 DEL are an aggressive B cell lymphoma and patients have a poor prognosis. IPI and bone marrow involvement were independent prognostic factors for DHL and DEL. BCL2, BCL6 and MYC rearrangements translocation, expression concurrent rearrangements and coexpression were were independent prognostic factors for survival. Potential implications: The present study analysed the genomic alterations and protein expression levels of MYC, BCL2 and BCL6 using FISH and IHC in Chinese patients with DLBCL.We assessed the frequency, clinicopathological features and the prognostic impacts of DHL and DEL in a cohort of de novo DLBCL patients and evaluated the role of each genetic translocation separately and in combination in order to provide reliable conclusions and practical recommendations for diagnostic workups and prognostic predictions.